Effects of cognitive task execution on stable and unstable surface balance. Issue 1 (1st January 2017) - Quesada, Peter M.; Geiger, Jeffery T.
Abstract: Compromised balance with respect to both stable and passively unstable surfaces can potentially affect performance of many occupational, recreational and daily living tasks. Many tasks that require some level of balance maintenance, however, also involve burdens on individuals' cognitive systems. Consequently the purpose of this project was to investigate the effects of performing cognitive tasks on stable surface and passively unstable surface balance performance. Participants in this study performed balance task on a passible unstable surface, as well as on a stable surface, with and without concurrent quantitative and language based cognitive tasks. Concurrent cognitive tasks did not demonstrate statistically significant effects on stable surface balance. For unstable surface balance, concurrent cognitive tasks had significant effects on trunk and arm segment angular velocities, while significant effects on movement of the passively unstable surface were not observed. The lack of cognitive task effects on stable surface balance suggests that such balance is well maintained with less than full attention. While overall unstable surface balance performance (i.e. unstable surface movement) was also not significantly affected by cognitive task execution, increased trunk and upper extremity movement during cognitive tasks suggests that cognitive tasks can trigger shifting of strategies for passively unstable surface balance.